Strategi Pengelolaan Sampah Sistem Zero Waste Di Kelurahan Pegesangan Kota Mataram - Silmi, Hayatus; Zitri, Ilham (Indonesian Journal Publisher, 2024)
This study aims to analyze the concept of zero waste, identify effective implementation strategies, assess the chances of success and establish an integrated waste management model for implementation in Pegesangan Village, Mataram City. This study uses descriptive and qualitative methods. The data sources for this study are primary data obtained directly from the government, private sector, universities, the community and information media. In addition, it is supported by secondary data obtained from documents, publications or literature related to zero waste system waste management strategies. The results of this study indicate that the lack of public awareness of the importance of waste management and the existence of traditional markets hinder the effectiveness of waste management and sorting, making it difficult to implement a zero-waste system in the Pegesangan Barat Village area. To overcome these obstacles, the Pegesangan Village Government implemented a